Implementasi Analytic Hierachy Process (AHP) Dalam Sistem Pengambilan Keputusan Pemilihan Metode Pembelajaran Riset Operasi - Simarmata, Justin Eduardo; Chrisinta, Debora (Program Studi Matematika, Universitas Nusa Cendana, 2023)
An implementation of learning methods have to be adjusted for each course including Research Operation. This course relies on the process of critical thinking, problem solving and concept understanding. The selection of an appropriate learning methods is required to obtain an optimum learning outcome. An analysis of an appropriate learning methods can be done using Analytic Hierarchy Process (AHP). In this paper, AHP is applied to analyse and hence make decisions on appropriate earning methods for studying Operations Research course. The criteria used consist of effectiveness (K1), lecturer ability (K2), specialization (K3) and test scores (K4). While the alternatives used are the learning methods carried out, namely: Problem Based Learning (a1), drill and exercise (a2) and Blended Learning (a3). Based on the priority weight of each alternative, it is obtained that the Problem Based Learning learning method has advantages in effectiveness criteria, Drill and Exercise have advantages in student test score results and Blended Learning has advantages in the ability of lecturers. In calculating the overall weight, Problem Based Learning gives the highest weight among the Drill and Exercise learning methods and Blended Learning.